2013
DOI: 10.1177/0145445513476085
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Mindfulness-Based Interventions for Supporting People With Intellectual Disabilities

Abstract: A number of studies have used mindfulness-based interventions to influence the behavior of people with intellectual disabilities, to improve their quality of life, and to reduce challenging behavior. The present review critically evaluates 18 studies and assesses the clinical and academic impact of their findings. Strengths identified included replicable methodological approaches, use of multiple baseline designs, strong construct and criterion validity, and consideration of the mechanisms by which mindfulness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 46 publications
0
28
0
Order By: Relevance
“…Other major themes in this body of research include increased acceptance of self and others (Ashcroft, Barrow, Lee, & McKinnon, 2012;Barton, 2011;Chadwick, Kaur, Swellam, et al, 2011;Frank & La Barre, 2011;Garland, Schwarz, Kelly, et al, 2012;Hick & Furlotte, 2010;Irving, Park-Saltzman, Fitzpatrick, et al, 2014;Malpass, Carel, Ridd, Shaw, et al, 2012;Milligan, Badali, & Spiroiu, 2013;Wilkinson-Tough, Bocci, Thorne, & Herlihy, 2010), and relaxation and an increased feeling of calm (Barton, 2011;Coholic, 2011;Frisvold, Lindquist, & McAlpine, 2012;Harper, Webb, & Rayner, 2013).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Other major themes in this body of research include increased acceptance of self and others (Ashcroft, Barrow, Lee, & McKinnon, 2012;Barton, 2011;Chadwick, Kaur, Swellam, et al, 2011;Frank & La Barre, 2011;Garland, Schwarz, Kelly, et al, 2012;Hick & Furlotte, 2010;Irving, Park-Saltzman, Fitzpatrick, et al, 2014;Malpass, Carel, Ridd, Shaw, et al, 2012;Milligan, Badali, & Spiroiu, 2013;Wilkinson-Tough, Bocci, Thorne, & Herlihy, 2010), and relaxation and an increased feeling of calm (Barton, 2011;Coholic, 2011;Frisvold, Lindquist, & McAlpine, 2012;Harper, Webb, & Rayner, 2013).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Other major themes identified in the body of qualitative literature are enhanced emotional regulation (Chadwick, Kaur, Swellam et al, 2011;Coholic, 2011;Dennick, Fox, & Walter-Brice, 2013;Garland, Schwarz, Kelly et al, 2012;Hick & Furlotte, 2010;Martin & Lichtenberger, 2002;Mehling, Wrubel, Daubenmire, et al, 2011;Milligan, Badali, & Spiroiu, 2013;Wongtongkam, Ward, Day, & Winefield, 2013), enhanced spiritual connection, (Frisvold, Lindquist, & McAlpine, 2012;Hick & Furlotte, 2010), and an increase in the overall well-being of participants (Harper, Webb, & Rayner, 2013;Hick & Furlotte, 2010;Martin & Lichtenberger, 2002;Mehling, Wrubel, Daubenmire, et al, 2011;Wongtongkam, Ward, Day, & Winefield, 2013).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Mindfulness-based interventions have consistently reported positive outcomes in modifying behaviour. A review evaluating the evidence to date (Harper 2013) identified 18 studies that used mindfulness either as a stand-alone intervention or as part of acceptance and commitment therapy or dialectical behaviour therapy. Ten of these studies recorded effects on aggressive behaviour and all ten reported reduction in aggression.…”
Section: Mindfulnessmentioning
confidence: 99%
“…The first four papers deal with parents and paid carers, followed by three papers that deal with individuals with intellectual disabilities, and one involving both the individuals with intellectual disabilities and their carers. The final paper adds to the rapidly growing number of reviews of the extant mindfulness literature in developmental disabilities (e.g., Harper et al 2013;Kearney 2013a, 2013b).…”
mentioning
confidence: 99%